Industrial synthesis of terephthalic acid in near/supercritical water - Housley, Samuel Duncan (2018)
Terephthalic acid is an industrial commodity chemical produced as an intermediate in the manufacture of polyethylene terephthalate polymer used in the manufacture of polyester textiles, plastic bottles and packaging material. This thesis undertakes an industrial assessment of an alternative process technology for the manufacture of this intermediate. It is divided into nine Chapters which can be summarised as follows.